Discovering social relationships across categories of online forums with reply-to capabilities - Sharifah Sheikhah Aljunied. (2011)
Social media is an ever-growing tool that has taken the world by storm over the recent years. It is a medium for people to connect with each other, regardless of their physical location. Online forums are a type of social media that allow users to discuss and share ideas over various topics. Some of the popular forums include Slashdot (htp://Slashdot.org) and Yahoo! Groups. For this project, Slashdot was used as the research material, as it provides a platform that allows users to comment on other users‟ post. This feature is called „reply-to capabilities‟. Forums with reply-to capabilities generally achieve much larger network because they contain multiple threads. The project goes into great depth in explaining the interface and source codes of Slashdot. The main aim was to find out if categorical user interest could be achieved by analyzing user commenting patterns across the various categories. 12 categories provided by Slashdot were tested.